(untitled) (Development Service Industry Management, 2024)
The contemporary business landscape is characterized by high dynamism and uncertainty. In such conditions, the ability of business organizations to quickly adapt to changes and create innovative solutions becomes a key success factor. Over the past 10-15 years, the "design thinking" paradigm has gained increasing popularity. As a customer-centric concept focused on identifying consumer value preferences and developing innovative solutions to meet them through a specific flow, it combines a particular mindset, a process, a methodology, a concept, and, more recently, a culture of design thinking. This article explores the phenomenon of design thinking as a human-centered methodology that revolutionizes the approach to solving complex problems. A detailed analysis of the evolution of the design thinking concept is conducted, tracking changes in its definition, scope of application, its core principles and stages, and examining the factors contributing to its popularization. Based on a review of the scientific literature, the author formulates an original definition of design thinking, emphasizing its multidisciplinary nature and focus on consumer needs. Particular attention is paid to the role of design thinking in shaping innovation culture, developing innovative products and services, and creating new business models.